Asian species of the genera Anahita Karsch 1879, Ctenus Walckenaer 1805 and Amauropelma Raven, Stumkat & Gray 2001(Arachnida: Araneae: Ctenidae) - Jäger, Peter (Zootaxa, 2012)
Specimens of the spider family Ctenidae from South, East and Southeast Asia were examined. Thirteen new species aredescribed: Anahita jinsi spec. nov. (male, female; China, Sichuan); Ctenus martensi spec. nov. (male; Nepal), Ctenuscladarus spec. nov. (male; Burma), Ctenus theodorianum spec. nov. (male, female; Laos, Oudomxai), Ctenus lishuqiangspec. nov. (female; China, Sichuan), Ctenus holthoffi spec. nov. (male, female; Laos, Champasak), Ctenus bayeri spec.nov. (male; Laos, Champasak); Amauropelma beyersdorfi spec. nov. (male; India, Himachal Pradesh), Amauropelmastaschi spec. nov. (male; India, Uttar Pradesh), Amauropelma ekeftys spec. nov. (male, ?female; India, Meghalaya),Amauropelma hoffmanni spec. nov. (male, female; Laos, Luang Nam Tha), Amauropelma jagelkii spec. nov. (male,female; Laos, Luang Prabang), Amauropelma annegretae spec. nov. (male, female; Laos, Luang Prabang). Ctenus simplexThorell 1897 (Luang Prabang, Vientiane) and C. robustus Thorell 1897 (Luang Nam Tha, Luang Prabang) are recordedfor the first time from Laos, and the female of C. simplex is described for the first time. Ctenus ramosus Thorell 1887, C.robustus and C. palembangensis Strand 1906 as well as internal copulatory structures of Anahita fauna Karsch 1879 areillustrated for the first time. Anahita feai (F.O. Pickard-Cambridge 1902) comb. nov., A. jucunda (Thorell 1897) comb.nov., A. denticulata (Simon 1884) comb. nov., A. smythiesi (Simon 1897) comb. nov. and Amauropelma fungifer (Thorell1890) comb. nov. are transferred from the genus Ctenus. The nomina nova “Ctenus karschi” and “Ctenus tamerlani” proposed by Roewer (1951) are recognised as unavailable and thus invalid names.